THEORETICAL STUDY OF THE REMOVAL OF THE TROPOSPHERIC FORMALDEHYDE BY REACTION WITH OH* AND NH3* RADICALS - Cjuno H., Jesús A. (2006)
In the context of atmospheric chemistry, two reactions radical-molecule of hydrogen abstraction have been studied. These are the OH' and NO3: radical (oxidizers agents in the troposphere) with formaldehyde in gas-phase. The calculations were carried out using the PM3 and <>. Ab initio methods of the UHF type. The results have allowed us to estimate the corresponding times of tropospheric permanency and the implications of these reactions in the removal of forrnaldehyde and similars from the low atmosphere.